Perlindungan Hak Anak Dalam Keluarga dan Tantangan Global Dalam Perspektif Al-Qur’an - dan Abd. Kholiq, Shofiyah (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2020)
Children are a mandate from Allah that must be guarded and protected, because children are assets of parents and assets of the nation. Islam pays great attention to children's rights and even gets appreciation as adults, because children are more sensitive to social problems in their environment , so that guidance, education and attention to children are of higher intensity so that they can go through the process of normal growth and development. Ironically in this era of globalization, it turns out that many children do not get the attention of their parents and even lose the moment of being with their parents so that many children choose their own way of life by imitating what they watch through their gadgets. Islam teaches that in matters of education for children, the family is the first madrasa and especially for children where their parents act as the first and foremost teachers as well. Therefore, when children's education in the family is carried out properly, the child's growth and development will be optimal and will give birth to a quality generation